STUDI KELAYAKAN FINANSIAL USAHATANI LADA (Piper nigrum L.) DI DESA MAWAI INDAH KECAMATAN BATU AMPAR KABUPATEN KUTAI TIMUR (Study of Financial Feasibility on the Pepper Farming (Piper nigrum L.) in Mawai Indah Village Batu Ampar Subregency East Kutai Regency) - WENDA NATALIA VERONIKA; TETTY WIJAYANTI (Universitas Mulawarman (University of Mulawarman), 2021)
The increase of pepper demand in Mawai Indah Village indicates pepper has opportunity to develop in that area. The aim of this research was to determine the financial feasibility of pepper farming in Mawai Indah Village, Batu Ampar Subregency, East Kutai Regency. The research was conducted during three months, from September 2017 to January 2018. Data required in this research were primary and secondary data. Primary data were obtained from interviews and discussions with respondents, while the secondary data were obtained from library studies. The sample was taken by using proportional random sampling. Data were analyzed by calculating of Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C Ratio), and Payback Period (PP). The results of research showed that NPV of IDR20,893,599,376.00 (NVP > 0), Net B/C Ratio of 53 (Net B/C >1), IRR value of 46.41% (IRR > i) and Payback Period of 5 years and 1 month. The pepper farming in Mawai Indah Village, Batu Ampar Subregency, East Kutai Regency is financially feasible to be cultivated.